Formação docente: desafios e possibilidades da formação do pedagogo a partir do PPC do curso de Pedagogia da UFT-campus de Miracema - Silva, Ana Lucia de Sousa (Universidade Federal do Tocantins, 2025)
This work presents an approach to pedagogy and pedagogue training considering the proposals that govern training through the course PPP and the theoretical framework of some authors such as: Libâneo (2001), Saviani (2020), Pimenta (2022), Gatti (2010), among others. A qualitative research approach seeking to answer the following question: How does the PPP of the pedagogy course address the challenges and pos-sibilities of pedagogue training? It is organized into three articulated chapters with the aim of getting to know the UFT pedagogy bear project – Miracema campus and under-standing and discussing the topic of teacher training based on the references con-tained in the course’s PPC. Finally, it is understood that this study can contribute to academic training and to society in general, offering elements to evaluate the peda-gogy course.